2019
DOI: 10.4314/ajcem.v20i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic methods versus PCR-RFLP for the identification of dermatophyte species isolated from patients with dermatophytosis in Egypt

Abstract: Background: Dermatophytes are major causative agents of cutaneous fungal infections worldwide. Identification of dermatophyte species is based on macroscopic and microscopic morphology on different culture media. Molecular methods such as PCR-RFLP are rapid, reliable and precise identification methods. This local study aimed to identify the spectrum of dermatophyte species among the studied patients population using different phenotypic and genotypic methods. Materials and methods: Hair, skin and nail specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In the present study, Tinea capitis was the main clinical manifestation agreeing with a study on African children 17 . A study in Egypt reported Tinea capitis (85.2%) followed by Tinea corporis (8.1%) and Tinea unguium (6.7%) in order were the most frequent cases 18 . This is concordant with our study.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, Tinea capitis was the main clinical manifestation agreeing with a study on African children 17 . A study in Egypt reported Tinea capitis (85.2%) followed by Tinea corporis (8.1%) and Tinea unguium (6.7%) in order were the most frequent cases 18 . This is concordant with our study.…”
Section: Discussionmentioning
confidence: 95%
“…However, phenotypic methods are time-consuming, requires experienced personnel due to identification overlap between species (Arabatzis et al, 2007;De Baere et al, 2010;Gohar et al, 2019), particularly in species with a degenerate appearance such as M. ferrugineum, because colonies may be similar to atypical (dysgonic) variants of M.…”
Section: Discussionmentioning
confidence: 99%
“…Precise species‐level identification of dermatophytes is mandatory to know the source of infection, whether zoophilic, anthropophilic or geophilic, and to apply proper treatment and control measures (Gohar et al., 2019 ). Conventionally, the identification of dermatophytes including Microsporum spp., especially M. canis , usually depends on phenotypical features, such as direct microscopy and in‐vitro culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation